2010
DOI: 10.1128/aem.01428-10
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Valine 171 in α-Helix 5 of Bacillus thuringiensis Cry1Ab δ-Endotoxin in Translocation of Toxin into Lymantria dispar Midgut Membranes

Abstract: The Cry1Ab ␦-endotoxin V171C mutant protein exhibits a 25-fold increase in toxicity against Lymantria dispar, which correlates with a faster rate of partitioning into the midgut membrane and slightly decreased protein stability. This is an insect-specific mechanism; similar results were not observed in Manduca sexta, another Cry1Ab ␦-endotoxin-susceptible insect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 12 publications
(7 reference statements)
0
14
0
Order By: Relevance
“…Crystal proteins from Bt belonging to the insecticidal three-domain Cry toxin family have long been the subject of both protein improvement efforts and structure–function studies 16 17 18 19 . Another major class of Cry proteins belonging to the β pore-forming bacterial toxin family has received far less attention.…”
Section: Discussionmentioning
confidence: 99%
“…Crystal proteins from Bt belonging to the insecticidal three-domain Cry toxin family have long been the subject of both protein improvement efforts and structure–function studies 16 17 18 19 . Another major class of Cry proteins belonging to the β pore-forming bacterial toxin family has received far less attention.…”
Section: Discussionmentioning
confidence: 99%
“…These authors found that a conservative change to phenylalanine (W73F, W210F, W219F) produced mutant toxins 3.3, 1.5, and 2.3 times more toxic than the parental toxin. In a similar study [89], two α-helix 5 Cry1Ab mutants (V171C and L157C) with a 25-fold and 4-fold increase in toxicity toward Lymantria dispar, respectively, were reported.…”
Section: Evolution By Site-directed Mutagenesismentioning
confidence: 64%
“…In this regard, it should be noted that unidentified characteristics of recombinant Bt-toxins in Bt-plants might affect binding and host specificity (Crickmore, 2005), while toxicity of recombinant Cry toxins may also be influenced by synergisms with endogenous plant metabolites or other extrinsic factors (Then, 2010). Further, the specificity of Bt-toxins is known to be largely determined by subtle differences in proteolytic processing (Haider et al, 1986), both toxicity and expression may be affected by single amino-acid changes in the polypeptide chain (Ward et al, 1988;Alzate et al, 2010), and differences in posttranslational modification mechanisms between prokaryotic and eukaryotic biological systems may influence the toxic potential of transgenic proteins (Franck-Oberaspach and Keller, 1997).…”
Section: Discussionmentioning
confidence: 99%